2017
DOI: 10.1080/10538720.2017.1408518
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between Black and gay community involvement and HIV-related risk behaviors among Black men who have sex with men

Abstract: Blackgay men must navigate identities and stigmas related to being gay and Black, and report higher HIV incidence relative to their white male counterparts although they report lower rates of drug use and risky sexual behaviors. This study examined whether closeness to the gay or Black community correlated with HIV related risk and protective behaviors. Data were drawn from uConnect, a population-based cohort study of YBMSM on Chicago’s South Side. The sample consists of 618 Black MSM ranging in age from 16–29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 80 publications
1
9
0
Order By: Relevance
“…Black and Latino youth in the U.S. experience stigma, discrimination, and racism [ 13 , 14 , 15 , 16 ]. As a result, many navigate social inequities and exclusions that place them at greater risk for HIV (e.g., poverty, limited access to quality healthcare, psychosocial stress) [ 15 , 16 , 17 ]. Presently, Black and Latino youth in the U.S. are more likely to report living in lower socioeconomic communities [ 18 ], lower rates of educational attainment [ 19 , 20 ], and limited access to quality healthcare, including for sexual and reproductive health [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Black and Latino youth in the U.S. experience stigma, discrimination, and racism [ 13 , 14 , 15 , 16 ]. As a result, many navigate social inequities and exclusions that place them at greater risk for HIV (e.g., poverty, limited access to quality healthcare, psychosocial stress) [ 15 , 16 , 17 ]. Presently, Black and Latino youth in the U.S. are more likely to report living in lower socioeconomic communities [ 18 ], lower rates of educational attainment [ 19 , 20 ], and limited access to quality healthcare, including for sexual and reproductive health [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Presently, Black and Latino youth in the U.S. are more likely to report living in lower socioeconomic communities [ 18 ], lower rates of educational attainment [ 19 , 20 ], and limited access to quality healthcare, including for sexual and reproductive health [ 21 ]. Collectively, these factors place Black and Latino youth at heightened vulnerability to HIV [ 15 , 17 ]. Additionally, HIV-related stigma remains a major barrier influencing HIV prevention in the U.S.…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that feeling connected to the broader LGBT community, or LGBT community connectedness (LGBT CC), can serve a supportive role for Black SMM (Miller et al, 2012; Strauss et al, 2017). LGBT CC also is linked to greater knowledge of PrEP and participation in health promotion programs (Hotton et al, 2018). However, feeling alienated from the LGBT community may negatively influence Black SMM’s perceptions of PrEP due to its close association with gay men in the U.S. Further, LGBT CC has been shown to mediate the association between homophobia and healthcare-related factors such as having a health care provider (Anderson-Carpenter et al, 2019).…”
Section: The Present Studymentioning
confidence: 99%
“…Barriers to PrEP utilization may include individual factors as well as social and structural barriers. Previous research has identified the following barriers to HIV prevention: difficulties accessing healthcare (e.g., lack of health insurance, geographic distance), infrequent routine healthcare utilization, socioeconomic difficulties, low self-perceived HIV risk, depressive symptoms, and HIV stigma [ 3 , 5 , 6 , 8 , 9 , 10 , 11 ]. Social support and resilience have been shown to reduce HIV risk and improve HIV prevention outcomes [ 4 , 6 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these factors have been important targets in interventions to promote PrEP use among BSMM; research on PrEP interventions in this population are limited, however. Recent studies include interventions utilizing social networks among SMM to improve PrEP initiation and other forms of HIV prevention [ 5 , 6 , 9 , 10 ]. Social network approaches may help reduce barriers through fostering a safe environment free from judgment and discrimination, providing greater understanding and acceptance, and improving peer resilience.…”
Section: Introductionmentioning
confidence: 99%